How to understand bisphenol A (BPA) information correctly: Is it safe for human health - Abidin, Akhmad Zainal (Indonesian Nutrition Association, 2024)
Bisphenol A (BPA) is a synthetic chemical widely used in consumer products like polycarbonate plastics and epoxy resins. This presentation examines the sources, prevalence, and health impacts of BPA, alongside regulatory measures to mitigate its risks. BPA, not naturally occurring, enters the environment via industrial waste and consumer product degradation.